Implementasi Pembelajaran STEM pada Materi Sistem Reproduksi Tumbuhan dan Hewan Terhadap Kemampuan Berpikir Ilmiah Peserta Didik SMP - Rahmi Agustina; Ismul Huda; Cut Nurmaliah (Universitas Syiah Kuala, 2020)
Learning science in Junior High School in Pidie district has not yet developed the ability to think scientifically. Leanears have not been able to do a problem analisis and argue with the evisidence and experience of the investigation. That are not given the opportunity to have learning activities that could improve their thinking, and then the equipment used in the process of teaching and learning on the concept of plants and animals reproduction are inediquate. It is proved by the laboratory space that has not been used and incompleted equipment. This study aims to determine the differences in the implementation of integrated STEM learning and STEM Silo on the ability to think scientifically on plant and animal reproduction concept in class IX Pidie State Junior High School. The approach used in this study was quantitative, the type of research was applied research; the method used is quasi-experimental, with the Nonrandomized control group pretest-posttest design. The population in this study amounted to 236 students and the sample to 75 students. The research procedure consisted of giving pretest, giving STEM integrated treatment in the experimental class and STEM silo in the control class, and giving posttest. The instrument for measuring scientific thinking ability is to use essay tests accompanied by rubrics. Data analysis consisted of normality test, independent t-test and ANOVA test. The results of the study showed there are diffences in the average value of scientific thinking integrated STEM class that is76.74 and STEM silos 61.64. The research is aimed at differing students ability to scientific thinking. The students are taught by using integeted STEM learning and STEM silo in the reproduction of animal plant material grade IX SMP